Evaluation of microleakage of three different types of pit and fissure sealants using invasive and non-invasive techniques (An in-vitro study) - Hiwa S. Khidir; Hemn M. Suleman (Erbil Dental Journal)
Backgrounds: The aims of this study were to; Evaluate the amount of in-vitro microleakage of three different types of pit and fissure sealants (Vertise Flow, Kerr), (Helioseal-F, IvoclarVivadent), (GC Fuji TRIAGE, GC corporation) and the effect of occlusal preparation on the leakage value. Methods: Sixty extracted human premolars randomly divided into 6 groups (n=10/group). Teeth fissures of three non-invasive groups (1, 3, 5) left intact, fissures of other three invasive groups (2, 4, 6) were opened up with ¼ round bur. Teeth fissures in group (1, 2) sealed with self-adhesive Vertise Flow, group (3, 4) Helioseal-F, while group (5, 6) fissures sealed with Glass Ionomer GC Fuji TRIAGE. The teeth thermocycled between 5±2°C and 55±2°C for 500 cycles with a dwell time of 30 seconds; All teeth sealed apically and coated within 1.5 mm of the sealant margin with two layers of nail varnish, then immersed in 1% Methylene blue solution. Subsequently, two buccolingual sections were made parallel to the long axis of tooth yielding 3 sections and 4 surfaces per tooth for microleakage analysis. The surfaces were scored 0 to 3 for the extent of microleakage using a binocular microscope at 25X magnification. Microleakage was analyzed by using paired t-test and ANOVA. Results: Invasive technique produced significantly less microleakage than Non-Invasive groups (P<0.05). In all six groups Helioseal-F in Invasive technique showed significantly the least degree of microleakage (P<0.05). Conclusion: Helioseal-F was the best material in terms of reduced microleakage. Invasive technique compared to non-invasive technique had produced less degree of microleakage.